2021
DOI: 10.1080/10872981.2021.2011606
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing learning communities to deliver an integrated undergraduate medical education curriculum

Abstract: Aim Learning communities (LCs) have been identified as a structure to support student wellness as well as create a positive learning environment and have been increasingly adopted in undergraduate medical education (UGME). In 2016, Michigan State University College of Human Medicine made curricular changes which integrated basic, social, and clinical sciences. One of the major strategies adopted to deliver this integrated curriculum was to create LCs that served as a central scaffold for students’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This competence is echoed in the literature. A recent survey of mentees who matched into plastic surgery residencies found that items related to a genuine interest in the mentee’s career and personal development and a willingness to set aside time for teaching as the highest-rated attributes (Ahmady et al, 2020; Barker et al, 2016; Braunreiter et al, 2022; Frosch & Goldstein, 2019; Vuk et al, 2021). The mentees from the same study also stressed the importance of one-on-one time with their mentor and listed mentors’ time constraints as a substantial barrier to the mentorship relationship (Barker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This competence is echoed in the literature. A recent survey of mentees who matched into plastic surgery residencies found that items related to a genuine interest in the mentee’s career and personal development and a willingness to set aside time for teaching as the highest-rated attributes (Ahmady et al, 2020; Barker et al, 2016; Braunreiter et al, 2022; Frosch & Goldstein, 2019; Vuk et al, 2021). The mentees from the same study also stressed the importance of one-on-one time with their mentor and listed mentors’ time constraints as a substantial barrier to the mentorship relationship (Barker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, and at the beginning of the new academic year, the year one medical students entering the programme replace the graduating cohort. LCs should be purposefully small to create a positive and effective learning environment 3 and they should also be as culturally diverse in nature and gender balanced as much as possible. 4 , 5 However, as each medical school is different, the number of communities, and the proportion of students in each and their diversity, will most likely be dictated by the size of the class and the demographics of the student population.…”
Section: Designing Learning Communitiesmentioning
confidence: 99%
“…Additionally, LCs aim to foster a culture of lifelong learning. 3 , 6 They therefore can be viewed as supportive networks that are characterised by collaborative and studious, yet social, environments.…”
Section: Designing Learning Communitiesmentioning
confidence: 99%
See 1 more Smart Citation